2001
DOI: 10.1111/j.1753-6405.2001.tb01833.x
|View full text |Cite
|
Sign up to set email alerts
|

Messages in alcohol advertising targeted to youth

Abstract: Objective: To assess young people's perceived messages in three ads for a vodka‐based, pre‐mixed alcohol beverage, and to assess the extent to which the ads appeared to be consistent with the industry's voluntary code. Method: Members of two convenience samples of young people (15–16 and 19–21 years) were each exposed to one of three advertisements. Respondents completed a post exposure questionnaire based on standard advertising copy testing procedures. Results: The most frequently nominated open‐ended respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 18 publications
5
58
0
1
Order By: Relevance
“…Studies of youth exposure to alcohol advertising have been criticized rightly for ignoring the messages in the advertisements, and focusing solely upon their frequency. Australian research has found consistently that alcohol advertisements contain imagery and messages that young people interpret as suggesting that alcohol consumption will have positive psychological and social outcomes [17,18]. The existing studies on alcohol in movies focus upon the frequency and duration of the alcohol portrayals and draw conclusions about their composite effect on young people's atti-tudes and behaviours.…”
Section: Alcohol Portrayals In Movies: Now We Know They're There Whamentioning
confidence: 99%
“…Studies of youth exposure to alcohol advertising have been criticized rightly for ignoring the messages in the advertisements, and focusing solely upon their frequency. Australian research has found consistently that alcohol advertisements contain imagery and messages that young people interpret as suggesting that alcohol consumption will have positive psychological and social outcomes [17,18]. The existing studies on alcohol in movies focus upon the frequency and duration of the alcohol portrayals and draw conclusions about their composite effect on young people's atti-tudes and behaviours.…”
Section: Alcohol Portrayals In Movies: Now We Know They're There Whamentioning
confidence: 99%
“…Both the Alcohol Beverages Advertising Code and the complaints management system operate under the structure developed by the AANA. However, in the late 1990s and early 2000s the effectiveness of the regulatory system was questioned (Jones and Donovan 2001;Jones and Donovan 2002), and there were increasing public calls for an overhaul of the regulatory system (Ligerakis 2003;Ryan 2003). Following a formal review of the ABAC by the Ministerial Council on Drug Strategy in 2003, the code was revised to improve its responsiveness and general accountability (National Committee for the Review of Alcohol Advertising 2003).…”
Section: Australiamentioning
confidence: 99%
“…Australian research has found that alcohol advertisements contain imagery and messages that young people interpret as suggesting that alcohol consumption will have positive psychological and social outcomes (Jones and Donovan 2001;Jones et al 2008;Jones et al 2009). Research from New Zealand has demonstrated that young people use alcohol (and alcohol brands) as a way of communicating their identity and that alcohol marketers are developing increasingly sophisticated messages and strategies to engage young people in this process (McCreanor et al 2005a;2005b).…”
Section: The Role Of Advertisingmentioning
confidence: 99%
“…These discourses allow 44 youngsters to explore the social importance of alcohol consumption among their peer groups and to gauge attitudes towards it. Focus group research has demonstrated that exposure to alcohol advertising can induce positive emotional reactions to advertised brands among teenagers (Jones & Donovan, 2001). It is difficult to determine from qualitative evidence what specific impact exposure to alcohol advertising has upon the onset of drinking, but it is apparent that young people draw upon what they see in promotional campaigns for alcoholic products in their conversations about drinking with their friends (Cragg, 2004).…”
Section: Qualitative Studiesmentioning
confidence: 99%